2021
DOI: 10.1002/pd.5988
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fetal endoscopic tracheal occlusion in fetuses with congenital diaphragmatic hernia and moderate lung hypoplasia

Abstract: Objective: To assess the effect of Fetal Endoscopic Tracheal Occlusion (FETO) on neonatal survival in fetuses with left congenital diaphragmatic hernia (CDH) and moderate lung hypoplasia.Study Design: CDH fetuses with moderate pulmonary hypoplasia (observed/ expected lung area to head ratio between 26% and 35%, or between 36% and 45% with liver herniation) were prospectively recruited. Included patients were matched to a control group who were ineligible for FETO. Primary outcomes were survival at 28 days, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…By including the largest sample size of CDH patients treated with FETO and a control group, our analysis provides more reliable evidence regarding the effects of 36 Severe Belfort (2017) 28 Deprest (2021) 12 Ruano (2012) 21 Style (2019) 32 Subtotal (95% CI) Total events…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By including the largest sample size of CDH patients treated with FETO and a control group, our analysis provides more reliable evidence regarding the effects of 36 Severe Belfort (2017) 28 Deprest (2021) 12 Ruano (2012) 21 Style (2019) 32 Subtotal (95% CI) Total events…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Total (95% CI) Deprest (2021) 13 Test for subgroup differences: chi 2 = 1.68, df = 1 (P = 0. 36 Deprest (2021) 13 Deprest (2021) 12 Ruano (2012) 21 Doné (2013) 22 Early FETO Deprest (2021) 12 Doné (2013) 22 Moderate Severe Deprest (2021) 13 Dhillon (2018) 29 Deprest (2021) 12 Style (2019) 32 Belfort (2017) 28 Late FETO Deprest (2021) 13 Cruz-Martínez (2022) 36 Deprest (2021) 13 Cruz-Martínez (2020) 34 Cruz-Martínez (2020) 34 Cruz-Martínez (2022) 36 Deprest (2021) 13 Deprest (2021) 12 Ruano (2012) 21 Deprest (2021) 12 Deprest (2021) 13 Severe Deprest (2021) 12 Ruano (2013) 23 Ruano (2011) 19 Ruano (2012) 21 Subtotal (95% CI) FETO on the prognosis of CDH compared with previous studies [7][8][9][10][11] . Our study has several novel findings.…”
Section: Total Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…prenatal diagnosis, standardized severity assessment in the second or early third trimester, live born after 30 weeks and all managed with a standardized postnatal protocol) and reporting all core outcomes 19 . For example, fetal surgeons from Queretaro, 20,21 Mexico concluded that in their setting with suboptimal neonatal management, the postnatal outcome of CDH is less favourable than that observed elsewhere. The same was earlier reported in a study from Brazil 22 .…”
Section: The Natural History Of Congenital Diaphragmatic Hernia Is Qu...mentioning
confidence: 99%